Post-Truth Politics in an Election Year: Digital Disinformation and Political Polarization in Indonesia and the United States - Adam, David Bani (Journal of Political Innovation and Analysis, 2025)
The phenomenon of post-truth politics is increasingly prominent in the context of elections, where emotions and personal beliefs influence public opinion more than objective facts. The 2024 elections in Indonesia and the United States show similar trends, with the rise of digital disinformation and the intensification of political polarization. This article aims to examine how disinformation and digital narrative manipulation become strategic instruments in political contestation in both countries. The research method used is a comparative-qualitative study with a critical discourse analysis (CDA) approach. Data were collected from social media (Twitter/X, Facebook, YouTube), online news archives, and digital campaign documentation during the election period. In addition, text mining was conducted to identify recurring patterns of disinformation narratives. The results showed that in both countries, political actors utilized social media algorithms to spread divisive emotional messages, create echo chambers, and reinforce group identity. In Indonesia, religious and ethnic issues are often exploited, while in the US, ideological polarization between liberal and conservative camps dominates. Both contexts show that disinformation is not just a technical glitch, but part of a deliberate and structured political strategy. This research highlights the urgency of digital literacy policies, algorithmic transparency, and the role of regulators to counter disinformation-based polarization ahead of elections.